Have walking and bicycling increased in the US? A 13-year longitudinal analysis of traffic counts from 13 metropolitan areas. (April 2019) - Le, Huyen T.K.; Buehler, Ralph; Hankey, Steve
Highlights: Estimated temporal trends in non-motorized traffic counts for 13 US cities. Bicycle traffic increased by 2–6% per year among 1, 215 count locations. Pedestrian traffic increased by 2–3% per year among 659 count locations. Bicycle facilities were positively associated with bicycle traffic at baseline. Temporal trends based on counts are higher than for self-report data (NHTS and ACS). Abstract: Local, state, and federal governments promote walking and bicycling in order to reduce emissions and improve public health. Tracking rates of bicycling and walking over time is important for assessing progress towards this goal. In the United States, most data are limited to cross-sectional self-report surveys (e.g., National Household Travel Surveys [NHTS]) or capture only the main commute mode (e.g., American Community Survey [ACS]). This study examines temporal trends (while controlling for spatial factors) of active travel in 13 US metropolitan areas between 2004 and 2016 (with 78% of counts occurring between 2010 and 2016) using repeated counts of bicycle and pedestrian traffic (n = 1319 count locations; 5554 bicycle and 5166 pedestrian counts). We used multilevel mixed-effects models to examine the multi-year trend in bicycling and walking during morning and afternoon peak periods. In the 5 out of 8 models where the temporal trend was statistically significant, we found that, on average, traffic volumes increased at a rate of 2–6% (bicycle) and 2–3% (pedestrian) per year among count locations, holding other variables constant. Presence of bicycle facilities (e.g., bicycle lanes, off-street trails) was positively associated with higher levels of bicycle traffic. Our results based on observed traffic patterns suggest larger increases in bicycling and walking as compared to the trends reported from the NHTS and ACS data. Quantifying the temporal trend from observed counts of traffic may aid policy makers and urban planners in assessing progress towards the goal of increasing bicycling and walking to reduce emissions and increase physical activity.